Good function and high patient satisfaction at mean 2.8 years after dual mobility THA following femoral neck fracture: a cross-sectional study of 124 patients - Tabori-Jensen S (Dove Medical Press, 2018)
Steffan Tabori-Jensen,1,2 Torben B Hansen,1,2 Søren Bøvling,1 Peter Aalund,1 Morten Homilius,1 Maiken Stilling1,2 1University Clinic for Hand, Hip and Knee Surgery, Regional Hospital West, Holstebro, Denmark; 2Department of Clinical Medicine, Aarhus University, Aarhus, Denmark Aims: Our aim was to investigate function, health status and satisfaction in patients treated with primary dual mobility (DM) total hip arthroplasty (THA) after displaced femoral neck fracture (FNF). Patients and methods: From 2005–2011, 414 consecutive FNF patients received Saturne DM THA. At a minimum of 1-year follow-up, 124 (95 women) were evaluated with Oxford Hip Score (OHS), Harris Hip Score (HHS), health-related quality of life (HRQoL) measure (EQ-5D) and two functional tests: Timed Up and Go (TUG) and Sit to Stand 10 times (STS). The FNF patients were matched 1:2 by age, sex and surgery date with patients receiving THA due to osteoarthrosis (OA group) and 1-year OHS and EQ5D were compared. FNF patients were matched by age and sex with the general population index (GPI) for EQ-5D comparison. Results: Patient age at surgery after FNF was mean 74.8 (range 30–92) years. At mean follow-up of 2.8 (range 1.0–7.7) years, mean EQ-5D score was 0.79 (SD 0.15) in the FNF group, which was similar to the matched GPI (p = 0.4), but lower (p = 0.014) compared to the OA group. Mean OHS was 36.4 (SD 9.5) in the FNF group and 38.4 (SD 7.2) in the OA group (p = 0.18). HHS in the FNF group was 78.7 (SD 15.5). Mean TUG time was 13.5 (SD 4.9) secs, and mean STS was 37.9 (SD 15.3) secs. Eighty nine percent (n = 111) of FNF patients were satisfied with the operation result. Conclusion: DM THA following displaced FNF provides a good functional result and quality of life in addition to high patient satisfaction. Keywords: dual mobility cup, femoral neck fracture, hip arthroplasty, EQ-5D, Oxford Hip Score, patient reported outcome measures